Early innate immune responses in European sea bass (Dicentrarchus labrax L.) following Tenacibaculum maritimum infection - Ferreira, Inês A.; Peixoto, Diogo; Losada, Ana Paula; Quiroga, María Isabel; Vale, Ana do; Costas, Benjamín (Frontiers in Immunology, 2023)
The marine aquaculture industry has been witnessing a worldwide emergence of tenacibaculosis, a poorly understood bacterial disease caused by Tenacibaculum maritimum that affects commercially important fish. So far, knowledge on the T. maritimum virulence mechanisms is scarce and the pathogen-host interaction operating in tenacibaculosis remain to be disclosed. This study aimed at contributing to a better understanding of this disease, by evaluating the early innate immune response triggered in European sea bass (Dicentrarchus labrax) by a bath-challenge with T. maritimum.Groups of sea bass were bath-challenged with T. maritimum (challenged fish) or mock-challenged.Undisturbed fish were used as controls (time 0). Samples of blood, liver and mucosal organs (skin, gills and posterior-intestine) were collected at 0 h (control) and at 6, 24, 48 and 72 h post-challenge (n=12). Mucosal organs were used for analysing the expression of immune-related genes by RT-qPCR, as well as blood samples for assessing haematological and innate humoral parameters and liver for oxidative stress assessment.An increased expression of il-1β, il8, mmp9 and hamp1 was detected in all mucosal organs of infected fish when compared with control and mock-challenged fish, suggesting a proinflammatory response against T. maritimum transversal to all organs. The faster induction of these pro-inflammatory genes was observed in the gills. Regarding the systemic response, challenged fish presented neutrophilia, monocytosis, signs of anemia, and a decrease of bactericidal and lysozyme activities in plasma. Almost no variations were observed regarding hepatic oxidative stress.The present study suggests that T. maritimum induces a local innate immune response upon bath infection not only in the skin of European sea bass, but also in the gills and posterior-intestine, likely triggered by the T. maritimum's capacity to adhere, colonize and damage these organs that can function as entry ways to bacteria, leading ultimately to the seen host's systemic response.• Bath-challenge with T. maritimum induces a pro-inflammatory response in fish mucosal organs;• The response was faster in the gills than in the skin and posterior-intestine;• Hemato-immunological parameters of challenged fish suggest a systemic response;